The impact of information sharing on supply chain adaptability and operational performance. Issue 2 (27th September 2021) - Yang, Lu; Huo, Baofeng; Gu, Minhao
Abstract : Purpose: This study looks beyond firm boundaries to depict supply chain (SC) adaptability and classifies it into internal, customer and supplier dimensions to investigate their performance implications, respectively. This study also examines the enablers of SC adaptability based on information processing theory. Design/methodology/approach: This study applies the structural equation modeling method to investigate relationships among SC information sharing, SC adaptability and operational performance using data collected from 216 manufacturers in China. Findings: Internal information sharing has a positive impact on three dimensions of SC adaptability, whereas supplier and customer information sharing only have a positive impact on supplier adaptability. Customer and supplier information sharing interact to positively influence the three dimensions of SC adaptability, while internal and customer information sharing interact to negatively affect customer adaptability. We also find that all the three dimensions of SC adaptability can enhance operational performance. Originality/value: This study contributes to providing a holistic definition of SC adaptability and classifies it into three dimensions. It also investigates antecedents and performance outcomes of SC adaptability.